Challenges experienced during rehabilitation after traumatic multiple rib fractures: a qualitative study. Issue 23 (6th November 2018) - Claydon, Jacqueline; Maniatopoulos, Gregory; Robinson, Lisa; Fearon, Paul
Abstract: Background: People with multiple rib fractures rarely receive rehabilitation aimed specifically at their chest wall injuries. This research explores patient perceptions of rehabilitation and recovery. Materials and methods: A qualitative study exploring how a purposive sample of 15 people with traumatic multiple rib fractures at a Major Trauma Centre in the United Kingdom make sense of their recovery. Data collected during one-to-one interviews 4 to 9 months after injury. Transcripts analysed using Interpretative Phenomenological Analysis. Results: Struggling with breathing and pain: Difficulties with breathing and pain were initially so severe ?it takes your breath away? and people felt scared they may not survive. These symptoms gradually improved but feeling "out of puff" often persisted. Life on hold: Healing was considered a natural process which people couldn't influence, creating frustration whilst waiting for injuries to heal. Many believed they would never fully recover and accepted limitations. Lucky to be alive: All participants expressed a sense of feeling lucky to be alive. The seriousness of injury prompted a change in attitude to make the most of life. Conclusion: Rib fractures can be painful, but also frightening. A rehabilitation intervention promoting pain management, normalises trauma and restores physical activity may improve recovery. Implications for Rehabilitation: Patients identified challenges with rehabilitation throughout the entire recovery journey, and their rehabilitation needs evolved with time. People find it difficult to regain pre-injury fitness even after their fractures heal and pain subsides. A belief there is nothing that can be done to help rib fractures contributed to people lowering their expectations of achieving a full recovery and developing a sense of "making do". Rehabilitation and patient education after traumatic multiple rib fractures should focus on improving pain management, respiratory fitness and emotional well-being.